Short-range wireless communication : fundamentals of RF system design and application - Bensky, Alan, 1939- (Communications engineering series., 2004)
The Complete Tool Kit for the Hottest Area in RF/Wireless Design! Short-range wirelesscommunications over distances of less than 100 metersis the most rapidly growing segment of RF/wireless engineering. Alan Bensky is an internationally recognized expert in short-range wireless, and this new edition of his bestselling book is completely revised to cover the latest developments in this fast moving field. Youll find coverage of such cutting-edge topics as: architectural trends in RF/wireless integrated circuits compatibility and conflict issues between different short-range wireless systems Zigbee and related new IEEE standards for short-range communications latest U.S. and international regulatory standards for spread spectrum, ultra wideband, and other advanced communications techniques Alan Bensky also thoroughly discusses the fundamentals of radio signal propagation, communications protocols and modulation methods, information theory, antennas and transmission lines, receivers, transmitters, radio system design, and how to successfully implement a short-range wireless system. All material has been carefully updated and revised to make it as technically up-to-the-minute as possible. The accompanying CD includes Mathcad worksheets to greatly simplify common design tasks and calculations. Youll also find coverage of Bluetooth, Wi-Fi and related 802.11 variants, digital modulation methods, and other essential information for planning and designing short-range wireless hardware and networks. This new edition will, like the first edition, be an invaluable reference for engineers and technical professionals who design, support, market, and maintain short-range wireless communications systems. * No other book contains EVERYTHING pertaining to short-range wireless design. * Covers all the hot topics like 802.11, Zigbee, Wi-Fi and Bluetooth. * Valuable CD-Rom included that will simplify the design process.